Refined clinical scoring in comparative EAE studies does not enhance the chance to observe statistically significant differences. Issue 10 (31st August 2016) - Tietz, Silvia M.; Zwahlen, Marcel; Haghayegh Jahromi, Neda; Baden, Pascale; Lazarevic, Ivana; Enzmann, Gaby; Engelhardt, Britta
Abstract : Considering the 3R rules of animal experimentation, we asked if refined scoring of experimental autoimmune encephalomyelitis (EAE) in mice improves documentation of clinical EAE allowing to perform a more powerful statistical analysis. Surprisingly, refined EAE scoring failed to improve statistical outcome comparing the overall disease courses between two groups of mice.